PERBEDAAN NAFKAH ISTRI MENURUT KHI DAN BIDAYAT AL-MUJTAHID - Itang Komar (Ahwaluna | Jurnal Hukum Keluarga Islam, 2024)
The meaning of living in a number of Arabic dictionaries cannot be separated from the legal concept of the meaning of living in the sense of a number of provisions in the form of materials given by a husband to his wife which are used to fulfill daily life. The same meaning is also stated by the Big Indonesian Dictionary. This understanding of livelihood is not found in the KHI or the Bidayat al-Mujtahid book. It is interesting to research what is meant by a wife's maintenance according to KHI, what is meant by a wife's maintenance according to Bidayat al-Mujtahid and how the wife's maintenance differs according to KHI and Bidayat al-Mujtahid This research aims to determine the meaning of wife's maintenance according to KHI, the meaning of wife's maintenance according to Bidayat al-Mujtahid and the differences in wife's maintenance according to KHI and Bidayat al-Mujtahid. The research method used is a qualitative approach, literature study and is descriptive. The qualitative method was chosen with the aim of obtaining in-depth data in natural conditions with the researcher as the key instrument that produces descriptive data from the things observed. The research results show that the definition of wife maintenance in KHI is not explained in detail, nor is it explained in Bidayat al-Mujtahid. There are differences in a wife's living according to KHI and Bidayat al-Mujtahid, namely in terms of: Scope of living, time required to provide a living, size of the amount of living, the person who is obliged to provide a living and the person who is obliged to earn a living.